ANALISIS KEBUTUHAN MATERIAL PADA PEKERJAAN STRUKTUR KOLOM DENGAN METODE KONVENSIONAL - Alfianarrochmah, Ilma; Putra , Rendi Maysa (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2026)
In infrastructure development, it is important to plan material requirements for column structure work. Columns are important elements in bearing the loads they receive, so accurate concrete volume calculations will ensure the columns have the required strength and stability in accordance with SNI 2847:2013 standards [1]. Columns are vertical structural elements in buildings that function to withstand vertical loads and channel them to the foundation [2]. The quality of a building structure depends on the accuracy of material requirement calculations. Errors in calculations can result in significant financial and material losses. Therefore, a study will be conducted related to the analysis of column material requirement calculations for elementary school buildings. The purpose of this study is to analyze the material requirements for floors 1, 2, and 3 and to identify the implementation methods used in column work for the Joglo Elementary School Building Construction. This study applies a quantitative descriptive method. Calculation of column work volume requirements was carried out manually as a learning experience. The results of this study are the total requirement for column reinforcement on the 1st floor; 19,635.9 kg, floor 2; 17,407.6 kg, and floor 3; 17,566.8 kg. Column formwork requirements on the 1st floor; 644 m2, 2nd floor; 546 m2, and 3rd floor; 553 m2. Column casting requirements for 1st floor; 67.30 m3, 2nd floor; 57.06 m3, and 3rd floor; 57.79 m3. The method of implementing column work in this project includes reinforcement work, formwork, casting, dismantling of formwork, and column concrete maintenance.